An Analysis of Indonesian Children Repatriation in Syria - Poerwoko Hadi Sasmito; Beniharmoni Harefa (Indonesian Journal of Criminal Law Studies, 2020)
Some Indonesians in refugee camps in Syria state they want to return to Indonesia. The plan to repatriate the Indonesian ex-ISIS then raises the pros and cons. Some consider that Indonesian citizen who have joined ISIS deserve to be given the opportunity to improve themselves and have a right to be returned to Indonesia if they really want to repent. Some are worried that the repatriation of Indonesian citizen who join ISIS would create new problems in Indonesia. The problem is that among them there are dozens of children, and they are not combatants who took up arms against Iraq and Syria. They just follow where their parents go. Using the normative juridical study method, this paper explains the potential impact that can arise on national security if the Indonesian government adopts a policy of repatriating Indonesian children who used to join ISIS. The results in this study then provide a prescription that should be carried out by the Indonesian government towards Indonesian children who used to join ISIS.